BEST PRACTICE OPTIMALISASI PENGGUNAAN CANVA DALAM PENULISAN FORMAL INVITATION DI KELAS XI SMK NEGERI 1 TANJUNG PALAS - DWI HARTATIK HANDAYANI MUKTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
Online learning is one solution for the world of education to continue teaching and learning activities in the current pandemic conditions. However, this will not come without challenges, one of which is the lack of student motivation in online learning, especially in writing activities. Writing skills are very important for every student to have from an early age. Writing activities will produce a product, one of which is a Formal Invitation text. The ability to write formal invitation texts is an ability that must be mastered by students. However, just like every time they learn something new, language learners will encounter various difficulties and obstacles in the learning process they undergo. To increase student motivation, teaching materials are needed to attract students' attention so that learning is not boring. Canva is an application that teachers can use to create interesting teaching materials, especially in making Formal Invitations. The purpose of this activity is to improve students' ability to be creative, especially in writing Formal Invitations using the Canva application. The money research methods carried out in this best practice are: 1) interview, 2) observation stage, 3) documentation, and 4) evaluation stage. Based on the results of expert assessments, the design of learning media using the Canva application, especially in making Formal Invitations, obtained a score of 75.31 percent with a decent category. While the results of student responses were limited to a score of 82.8 percent with a very decent category. So from the results of expert assessments and the results of student responses, it shows that the learning media using the Canva application is feasible and easy to use. Not only English subjects, other subjects can also use the Canva application as a learning medium, both in online and offline learning. ABSTRAKPembelajaran daring merupakan salah satu solusi dunia pendidikan untuk tetap melakukan kegiatan belajar mengajar dalam kondisi pandemi sekarang ini. Namun, hal ini pun tidak akan datang tanpa tantangan, salah satunya adalah kurangnya motivasi siswa dalam belajar daring, khususnya dalam kegiatan menulis. Keterampilan menulis sangatlah penting untuk dimiliki setiap siswa sejak dini. Kegiatan menulis akan menghasilkan sebuah produk, salah satunya teks Formal Invitation. Kemampuan menulis teks undangan res Formal Invitation merupakan kemampuan yang harus dikuasai oleh siswa. Namun, layaknya juga dalam setiap belajar sesuatu yang baru, pembelajar bahasa akan menemui berbagai kesulitan dan kendala dalam proses pembelajaran yang dijalaninya. Untuk meningkatkan motivasi siswa, maka diperlukan bahan ajar menarik perhatian siswa sehingga pembelajaran tidak membosankan. Canva merupakan aplikasi yang dapat digunakan guru untuk membuat bahan ajar menarik khususnya dalam pembuatan Formal Invitation. Tujuan dari kegiatan ini adalah meningkatkan kemampuan siswa dalam berkreasi khususnya dalam penulisan Formal Invitation menggunakan aplikasi Canva. Adapun metode penelitian uang dilakukan dalam best practice ini adalah: 1) wawancara, 2) tahap observasi, 3) dokumentasi, dan 4) tahap evaluasi. Berdasarkan hasil penilaian ahli, desain media pembelajaran menggunakan aplikasi Canva khususnya dalam pembuatan Formal Invitation diperoleh skor 75,31 persen dengan kategori layak. Sedangkan hasil tanggapan siswa secara terbatas diperoleh skor 82,8 persen dengan kategori sangat layak. Sehingga dari hasil penilaian ahli maupun hasil tanggapan siswa menunjukkan bahwa media pembelajaran menggunakan aplikasi Canva layak dan mudah untuk digunakan. Tidak hanya mata pelajaran Bahasa Inggris, mata pelajaran yang lain pun dapat menggunakan aplikasi Canva ini sebagai media pembelajaran, baik dalam pembelajaran daring maupun luring.